Skuteczność leczenia migreny akupunkturą u kobiet z zespołem menopauzalnym stosujących hormonalną terapię zastępczą i niestosujących hormonalnej terapii zastępczej - Piotr Woźniak; Ewa Ziółkowska; Tomasz Stetkiewicz; Przemysław Oszukowski (Menopause Review, 2011)
Background: Migraine because of a high morbidity rate generates high expenses for the health-care systemand also for the patients. It triggers decrease of life comfort and frequently obstructs normal functioning. Allauthors of studies pay attention to definite higher incidence in women. Not in all patients is pharmacotherapyeffective; some of them decide on acupuncture exams. Simultaneously women between 48 and 52 years of lifesuffer from menopause. Some of them decide to take hormonal replacement therapy. Aim of the study: In the research we retrospectively subjected to evaluation the effect of therapeuticacupuncture exams carried out because of occurrence of migraine in a group of women in menopausal stage,in two groups: applying and not applying hormonal replacement therapyMaterials and methods: Medical examination survey of 48 patients aged 49-55 with migraine not respondingto pharmacological treatment; 25 of them administer transdermal hormonal replacement therapy. All of patientsundergo a whole cycle of 10 acupuncture treatments. Patients before the first exam and after the whole cycleanswered the question in the questionnaire elaborated for the needs of this research. Furthermore, under usageof acupuncture treatment patients rate its analgesic effectiveness with a ten-point scale.Results: In the group of patients applying HTZ pain ailments regression was faster.Conclusion: Acupuncture is a safe method and recommended in treating migraine. Usage of HTZ in patientspositively influences results of acupuncture therapy.